Liposomal Aloe vera trans-emulgel drug delivery of naproxen and nimesulide: A study - Venkataharsha, Panuganti; Maheshwara, Ellutla; Y, Prasanna Raju; Reddy, Vayalpati Ashok; Rayadu, Bandugalla Sanjeev; Karisetty, Basappa (International Journal of Pharmaceutical Investigation)
Introduction: The present aim of this study was to formulate naproxen and nimesulide liposomal formulation for incorporation in Aloe vera transemulgel and to carry out in vitro and in vivo evaluation of the formulation. Material and Methods: A. vera gel was prepared and used as a gel base for formulation. Carbopol 934 is used as a gelling agent and Methyl paraben was used as a preservative for the formulation of the gel. Liposomes was formulated by using hydration method. The formulated naproxen and nimesulide liposomal formulation using A. vera trans-emul gel were evaluated for in vitro studies such as drug release, permeation study, and drug content and entrapment efficiency. Paw edema method in Wistar rats induced by carrageenan is used to study in vivo anti-inflammatory action. Result: From the in vitro studies such permeability drug release naproxen 65% (69.6), Nimesulide 65% (61.1), and commercial Nimsulide gel (60.82) at 240 min. In vivo data shows that formulated liposomal transemulgel formulation are superior in their efficacy compared to commercial and A. vera gel. The results are compared with the commercial formulations. Conclusion: From our results, it is concluded that the A. vera trans emul gel using nimesulide and naproxen liposomal formulation is stable and prepared gel base is effective for formulation with high drug release and drug content compared with commercial formulation with significant anti-inflammatory effect.
Keywords: Aloe vera; drug release; emul gel; liposomes; naproxen; nimesulide; paw edema; peremeation studies